(untitled) (Lex Scientia Law Review, 2026)
The development of health technology must be accompanied by the establishment of robust healthcare laws to safeguard both healthcare professionals and patients from potential risks and losses arising from errors in telesurgery. In light of this, three key issues are formulated in this study: namely the development of telesurgery in the legal framework, the legal construction of telesurgery and legal responsibility in the event of errors in telesurgery. This study is a normative legal analysis examining the regulatory framework governing telesurgery and the legal responsibilities arising from potential errors. A literature review serves as the primary method for collecting both primary and secondary legal sources. The research employs a legislative and conceptual legal approach, with qualitative analysis used to address the identified issues. Legal frameworks for the regulation of telesurgery must be developed at both the international level, particularly in relation to jurisdiction, and the national level, focusing on medical standardization in its implementation. The practice of telerobotic surgery must be regulated by law, derived from policy regulations, and regulated by internal guidelines from surgeons. At a minimum, several legal elements must be addressed, including jurisdiction, ethics committees within surgical organizations, inter-ministerial collaboration, the legal relationship between patients and physicians, pre-operative explanations and informed consent, legal accountability, medical confidentiality, medical team requirements, and information security management systems. Legal liability for failed surgical procedures may arise in cases of errors, whether intentional or due to negligence.